Particle size and zeta potential investigation of synthetic peptide-protein conjugates - Derman, Serap; Akdeste, Zeynep Mustafaeva (WALTER DE GRUYTER GMBH, 2015)
Objective: Synthetic peptides are not sufficiently large or complex by themselves to induce immune system because of their small size. Synthetic peptides are usually conjugated to different carriers such as proteins and polyelectrolytes to enhance their immunogenic properties and antigen-specific antibody production (Abs) rate. Thus, the aim of this study is synthesis of peptide-protein covalent conjugates, and size and zeta potential analysis of these conjugates. Methods: In this study, synthetic peptide antigen of the 135-161 amino acids sequence of immunogenic VP1 capsid protein of A type foot-and-mouth disease virus (FMDV) was covalently conjugated to bovine serum albumin (BSA) with the carbodiimide method by using 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide hydrochloride (EDC) at different molar ratios of peptide (y=n(Peptide)/n(BSA)). Particle size and zeta potential analysis of peptide-protein bioconjugates have been performed by using dynamic and electrophoretic light-scattering methods. Results: The size and surface charge of bioconjugates are important factors in a synthetic peptide vaccine. Nevertheless, there virtually no research has been conducted on zeta potential and the size of peptide-protein bioconjugates detailed. Conclusion: Dynamic and electrophoretic light scattering analyses clearly demonstrated that zeta potential of the FMDV 135-161 synthetic peptide-BSA conjugates shifts to less negative potentials and particle sizes increase as the amount of peptide increased in conjugates. The data about peptide-carrier protein conjugates obtained by using these methods are very important for developing peptide-based vaccines.
Keywords: Particle size; Zeta potential; Synthetic peptide; Conjugation; Foot and mouth disease; Bovine serum albumin; BOVINE SERUM-ALBUMIN; PERFORMANCE LIQUID-CHROMATOGRAPHY; MOUTH-DISEASE; HYDRODYNAMIC SIZE; POLYACRYLIC-ACID; SWISS-MODEL; VACCINE; ANTIBODIES; EPITOPE; NANOPARTICLES; Biochemistry & Molecular Biology